2007
DOI: 10.1080/07434610701553668
|View full text |Cite
|
Sign up to set email alerts
|

AAC for adults with acquired neurological conditions: A review

Abstract: The purpose of this review is to describe the state of the science of augmentative and alternative communication (AAC) for adults with acquired neurogenic communication disorders. Recent advances in AAC for six groups of people with degenerative and chronic acquired neurological conditions are detailed. Specifically, the topics of recent AAC technological advances, acceptance, use, limitations, and future needs of individuals with amyotrophic lateral sclerosis (ALS), traumatic brain injury (TBI), brainstem imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(124 citation statements)
references
References 42 publications
2
117
0
5
Order By: Relevance
“…This research has established empirical evidence of the positive impact of AAC (Beukelman et al, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken et al, 2012;Ganz et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Walker & Snell, 2013;Wendt, 2009) and has demonstrated that these gains come at no risk to speech development or recovery (e.g., Millar, Light, & Schlosser, 2006;Romski et al, 2010). As a fi eld, we should take pride in this increased research base that has resulted in advances in evidence-based AAC services.…”
Section: Research To Advance Understanding Of Communicative Competencementioning
confidence: 99%
See 2 more Smart Citations
“…This research has established empirical evidence of the positive impact of AAC (Beukelman et al, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken et al, 2012;Ganz et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Walker & Snell, 2013;Wendt, 2009) and has demonstrated that these gains come at no risk to speech development or recovery (e.g., Millar, Light, & Schlosser, 2006;Romski et al, 2010). As a fi eld, we should take pride in this increased research base that has resulted in advances in evidence-based AAC services.…”
Section: Research To Advance Understanding Of Communicative Competencementioning
confidence: 99%
“…Operational skills involve skills in the technical operation of AAC strategies and techniques, including: (a) skills to produce the hand or body positions, shapes, orientations, and movements for gestures, signs, or other forms of unaided communication (e.g., eye blink codes, head nod/shake); (b) skills to utilize selection technique(s) for aided AAC systems (e.g., direct selection with a fi nger or fi st, eye gaze, scanning with a single switch); and, (c) skills to navigate and operate aided AAC systems accurately and effi ciently (e.g., navigate between pages, enter codes to retrieve pre-stored vocabulary items). These operational skills must extend across the full range of modes used by the individual with complex communication needs, including both unaided and aided means of communication, and both low tech and high tech systems (Beukelman, Fager, Ball, & Dietz, 2007;Hodge, 2007). Randy Horton described the signifi cant demands of learning the operational skills for a single AAC system (approximately 96 hours in Randy ' s case) and the lack of instruction typically provided to support the development of these skills:…”
Section: Adequacy Of Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 30-40 years, there have been substantial changes to these practices. There is now a growing body of empirical evidence documenting the positive outcomes of AAC intervention (e.g., Beukelman, Fager, Ball, & Dietz, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken, Beukelman, & Hux, 2012;ganz, et al, 2011;Machalicek et al, 2010;Schlosser, Sigafoos, & Koul, 2009;Wendt, 2009). Moreover, there is evidence that AAC interventions pose no risk to speech development or recovery (e.g., Beukelman & Mirenda, 2013;Millar, Light, & Schlosser, 2006;Schlosser & Wendt, 2008).…”
Section: Increased Awareness and Acceptance Of Aacmentioning
confidence: 99%
“…In addition, increasing numbers of speech language pathologists are working to reconcile the traditional restorative approaches to language intervention (utilized historically with individuals with aphasia) with AAC interventions that focus on functional communication for these individuals (SimmonsMackie, King, & Beukelman, in press). Increased awareness and acceptance of AAC have also resulted in its successful application to new populations of adults with acquired disabilities, including individuals with primary progressive aphasia, Alzheimer's disease and dementia, and those in intensive care units (ICU) who may have temporary conditions (e.g., Beukelman et al, 2007;Bourgeois, Dijkstra, Burgio, & Allen-Burge, 2001;Cress & King, 1999;Fried-Oken, Rau, & Oken, 2000;Fried-Oken, Rowland et al, 2012;Downey & Hurtig, 2006).…”
Section: Increased Awareness and Acceptance Of Aacmentioning
confidence: 99%